2009
DOI: 10.1002/stem.222
|View full text |Cite
|
Sign up to set email alerts
|

CXCR2 Mediates the Recruitment of Endothelial Progenitor Cells During Allergic Airways Remodeling

Abstract: Airway remodeling is a central feature of asthma and includes the formation of new peribronchial blood vessels, which is termed angiogenesis. In a number of disease models, bone marrow-derived endothelial progenitor cells (EPCs) have been shown to contribute to the angiogenic response. In this study we set out to determine whether EPCs were recruited into the lungs in a model of allergic airways disease and to identify the factors regulating EPC trafficking in this model. We observed a significant increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 50 publications
(80 reference statements)
1
52
0
Order By: Relevance
“…CXCR2 is expressed by EPCs in both humans and rodents (27,28). Recently, it has been shown that the ligation of CXCR2 with its ligands, CXCL1 and CXCL2, is critical for EPC recruitment into the lung of allergen-sensitized mice (29). In our FIGURE 8.…”
Section: Discussionmentioning
confidence: 69%
“…CXCR2 is expressed by EPCs in both humans and rodents (27,28). Recently, it has been shown that the ligation of CXCR2 with its ligands, CXCL1 and CXCL2, is critical for EPC recruitment into the lung of allergen-sensitized mice (29). In our FIGURE 8.…”
Section: Discussionmentioning
confidence: 69%
“…tor cell recruitment and the angiogenic response in this model of allergic inflammation of the airways (45). Human mast cells are both a source and a target of angiogenic factors and therefore might play a role in inflammatory and neoplastic angiogenesis through the expression of several forms of VEGFs and their receptors (46).…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, depending on disease status, the concentrations of CXCL1 measured in biological fluids of humans or animal models do not exceed 10 ng/ml (18,54,55). Therefore, using a narrower range of concentrations of CXCL1 to examine its effect on ASMC migration may better reflect its biological significance in asthmatic airways remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Although primarily known as a potent inducer of neutrophil chemotaxis (16), CXCL1 was shown to induce cancer cell invasion (17) and endothelial (18) and epithelial cell migration (19). CXCL1 facilitates its signaling by binding to its putative receptor, the chemokine receptor CXCR2, although it also was found to bind to CXCR1, albeit with lower affinity (20).…”
mentioning
confidence: 99%